Culture and Consumption: A Theoretical Account of the Structure and Movement of the Cultural Meaning of Consumer Goods - McCracken, Grant (Journal of Consumer Research, 1986)
Abstract Cultural meaning in a consumer society moves ceaselessly from one location to another. In the usual trajectory, cultural meaning moves first from the culturally constituted world to consumer goods and then from these goods to the individual consumer. Several instruments are responsible for this movement: advertising, the fashion system, and four consumption rituals. This article analyzes the movement of cultural meaning theoretically, showing both where cultural meaning is resident in the contemporary North American consumer system and the means by which this meaning is transferred from one location in this system to another.